A new species of the genus Sinanapis Wunderlich & Song (Araneae, Anapidae) from China - Jin, Chi; Zhang, Feng (Zootaxa, 2013)
Anapidae are small-sized ( 3 mm), three-clawed, haplogyne spiders with six or eight eyes situated on an elevated ocular region and an anterior labral spur. The family currently contains 38 genera and 153 species worldwide (Platnick 2013, Lin, Li & Jäger, 2013). Nine species belonging to six genera have been recorded from China (Oi, 1960; Brignoli 1981; Zhang & Chen, 1994; Wunderlich & Song, 1995; Ono, Chang & Tso, 2006; Miller, Griswold & Yin, 2009; Lin & Li, 2012).